Employability of Postgraduate Scholars in Rajasthan (Indian Journal of Extension Education, 2018)
The study of the employability of postgraduate scholars was conducted in the state of Rajasthan by selecting three agriculture universities MPUAT (Udaipur), SKNAU (Jobner), SKRAU (Bikaner) purposively from among three universities 90 respondents were selected randomly. The basic information regarding the postgraduate research scholars was collected from the P.G. & Ph.D scholars. Thirteen components were selected as indicators of overall employability of postgraduate scholars. The overall distribution of employability shows that a great majority of the postgraduate scholars (72.22 per cent) studying in Agricultural Universities in Rajasthan expressed medium level of overall employability. Separately employability of the postgraduate scholars (70 per cent) studying in MPUAT (RCA) Udaipur was high. About 63.33 per cent of the scholars studying in SKNAU (Jobner) and 90 per cent of the postgraduate scholars studying in SKRAU (Bikaner) were from medium level of employability respectively.